Inequity in access to health and racism: epidemiological analysis during the COVID-19 pandemic/ Desigualdad en el acceso a la salud y racismo: análisis epidemiológico durante la pandemia de COVID-19/ Iniquidades no acesso à saúde e racismo: análise epidemiológica durante a pandemia de COVID-19 - Rosa, Maria Fernanda Prado; Nicoleti Turazza da Silva, William; Pio Gomes Faria, Carolina; Ferreira Rende, Vinícius; Vilges de Oliveira, Stefan; Raimondi, Gustavo Antonio (Journal Health NPEPS, 2021)
Objective: to analyze the epidemiological data of Severe Acute Respiratory Syndrome (SARS), and the access to health of black people in Brazil during the pandemic, comparing them with previous years. Method: epidemiological, descriptive, and quantitative study of SARS cases in black patients, reported in the information system on epidemiological surveillance of influenza of the Ministry of Health, between 2017 and 2020. Results: it was observed that, in 2020, there was an increase in the prevalence of SARS cases in blacks, in addition to a significant increase in lethality when compared to the general population. Furthermore, it was found that mortality was significantly higher in individuals with SARS who required ventilatory support. Conclusion: skin color is a determinant of several social and health vulnerabilities in Brazil and worldwide, having a direct impact on the increased morbidity and mortality of the black population during the pandemic.